2012
DOI: 10.1007/s00431-012-1843-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life of patients treated in paediatric intensive care unit

Abstract: Acute illness has a significant impact both on children with and without CHC after treatment in PICU 6 months after discharge. Twenty-four months after discharge, comorbidity was identified as the decisive factor for diminished QOL in children after PICU treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Preexisting neurodevelopmental disease was a risk factor in one study (50), but this was contradicted in another study (41). In the first study, patients were at relatively good baseline function and neurologic deficits were likely mild (50), whereas in the second study, majority of the children had severely poor function prior to admission (41).…”
Section: Factors Associated With Acquired Functional Disabilitymentioning
confidence: 91%
See 4 more Smart Citations
“…Preexisting neurodevelopmental disease was a risk factor in one study (50), but this was contradicted in another study (41). In the first study, patients were at relatively good baseline function and neurologic deficits were likely mild (50), whereas in the second study, majority of the children had severely poor function prior to admission (41).…”
Section: Factors Associated With Acquired Functional Disabilitymentioning
confidence: 91%
“…Of particular importance is the rate of acquired functional impairment from critical illness as opposed to preexisting disease (76,77). Acquired functional impairment in a general PICU population ranged from 10% to 36% at discharge, to 26% at 6 months, and 10% to 13% when followed up at more than 2 years (5,37,39,41,44,46,47,50). A longitudinal study demonstrated that some impairment resolves with time as acquired impairment dropped from 26% at 6 months to 19% at 2 years after PICU admission (50).…”
Section: Functional Outcomes In Picu Survivorsmentioning
confidence: 97%
See 3 more Smart Citations